Protein losing enteropathy and pneumatosis intestinalis in a child with COVID 19 infection - Pejman Rohani; Abdollah Karimi; Sedigheh Rafiei Tabatabaie; Mitra Khalili; Aliakbar Sayyari (Elsevier, 2021)
Background: Severe acute respiratory syndrome corona virus 2 (SARS- CoV-2) is known as COVID 19 seems to be one of the most contagious and dangerous infection in children and adults. According to first adult studies association of gastrointestinal (GI) symptoms with COVID 19 infection was as high as 79% (1).But later study showed lower association around 18% (2).As the pandemic of COVID 19 is going on, different clinical presentation of disease especially in children are well appeared. In addition atypical presentations may confuse and mislead physician to do different diagnostic procedures and interventions. We report a 6 years and half old boy with diarrhea, abdominal pain with first diagnosis acute abdomen due to acute appendicitis. At last diagnosis of pneumatosis intestinalis due to enterocolitis was confirmed. Case presentation: A 6 years and half old boy with severe abdominal pain admitted in emergency ward. He had history of fever, nine days of diarrhea and recurrent vomiting. The abdominal pain was severe with moderate tenderness in right lower quadrant. He admitted in pediatric surgery ward after surgical consultation for rolling out acute appendicitis. The results of first lab studies were shown leucopenia, lymphopenia and COVID 19 PCR was positive. During admission the cough has increased and abdominal distention has evolved. Vomiting was intractable and feeding was impossible. Pneumatosis intestinalis in ascending colon and dilatation in colon caliber were detected abdominal. Miliary like pattern in lung has reported in chest CT. Stool exam results revealed loss of protein in high amount in spite of normal pancreatic and enterocyte function. The calprotectin was high and implied high inflammation in large intestine. With all above data necrotizing enterocolitis management was started. After 14 days patients had good appetite and feeding slowly introduced. All symptoms resolved with exception of cough. Albumin and other electrolytes remained stable. The patient discharged without morbidity. Conclusion: COVID 19 infection has many different and mysterious presentations. GI manifestations are among important, common presentations. The acute abdomen like presentation with different complications like pneumatosis intestinalis, protein losing enteropathy are not common but knowledge about these presentations assist physician to be aware and make decision accurately.